2021
DOI: 10.3390/ijerph18062992
|View full text |Cite
|
Sign up to set email alerts
|

Psychological (In)Flexibility Mediates the Effect of Loneliness on Psychological Stress. Evidence from a Large Sample of University Professors

Abstract: Psychological stress, loneliness, and psychological inflexibility are associated with poorer mental health and professional performance in university teachers. However, the relationship between these variables is understudied. The aim of the present study is to analyze the mediating role of psychological (in)flexibility on the effect of loneliness on psychological stress. A total of 902 professors from 11 universities in Ecuador were analyzed using standardized scales: the Perceived Stress Scale (PSS-14) to as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 48 publications
0
8
0
3
Order By: Relevance
“…Teacher burnout in online higher education is an interesting topic not only under the umbrella of the pandemic, but also in a normal situation. Hence, several scholars have pointed out that teaching is a stressful profession [4,24] and the levels of teacher burnout are not trivial. Considering that teacher burnout and feelings of isolation can lead to demotivation, negative feelings, dissatisfaction, extremely low levels of efficiency, and low levels of optimism [4], with severe consequences on the physical and mental health of teachers [23,24], teacher burnout is a matter of concern.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Teacher burnout in online higher education is an interesting topic not only under the umbrella of the pandemic, but also in a normal situation. Hence, several scholars have pointed out that teaching is a stressful profession [4,24] and the levels of teacher burnout are not trivial. Considering that teacher burnout and feelings of isolation can lead to demotivation, negative feelings, dissatisfaction, extremely low levels of efficiency, and low levels of optimism [4], with severe consequences on the physical and mental health of teachers [23,24], teacher burnout is a matter of concern.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Lowenstein [ 36 ] suggested that isolation, lack of support, absence of social recognition, large class size, fear of violence, absence of classroom control, role ambiguity, and limited promotional opportunities contribute to teacher burnout. Ortega-Jiménez et al [ 24 ] documented that psychological stress, loneliness, and psychological inflexibility are related with poorer mental health and professional performance in a sample of 902 university teachers. As Pyhältö et al [ 12 ] explained, several empirical studies have revealed that social interrelations can enhance teachers’ well-being, and, in particular, positive relationships with colleagues decrease teachers’ stress.…”
Section: Literature and Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…McLean and Connor (2015) and Roberts et al (2016) found that depressive symptomology among teachers was related to poorer student achievement and social-emotional development. Ortega-Jiménez et al (2021) demonstrated that psychological flexibility, or the ability to experience the present moment with an open mind, mediated the relationship between loneliness and stress among professors.…”
Section: Teacher Stressmentioning
confidence: 99%
“…Thus, the causes of burnout must be sought not only in objective conditions ( Garcia et al, 2015 ) but mainly, in the individual’s interaction with those conditions, mediating by other psychosocial variables, such as personality, emotional regulations, as well as the perceptions, evaluations, and expectations of people ( Salami and Ajitoni, 2016 ; Bang and Reio, 2017 ; Hwang et al, 2019 ; Ortega-Jiménez et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%